Environment-Based Interactive Multimedia to Improve Learning Outcomes in Natural Science Learning Content - I Gusti Agung Made Dana Putra; Desak Putu Parmiti (Universitas Pendidikan Ganesha, 2023)
Not utilizing learning media causes a lack of understanding of the material, which causes students not to understand the lesson. Students need to be motivated to follow the lesson, which causes them to lose focus during the learning process. This study aims to develop Environment-Based Interactive Multimedia in Science Content in Class V SD. This type of research is developed using the ADDIE model. The subjects of this research were one learning content expert, one learning design expert, and one learning media expert. Product trials were carried out on students, 3 for individual trials and 9 for small group trials. Methods of collecting data in this study using questionnaires and tests. The data collection instrument is in the form of a questionnaire. The techniques used to analyze the data are descriptive qualitative analysis, quantitative, and inferential statistics. The result of the research is the assessment made by subject matter experts, which is 94.6% (very good). The assessment results by learning media experts were 95.7% (very good). Assessment based on the results of individual trials gets a score of 91% (very good). The results of the small group trial obtained a score of 81.83% (good). The results of the t-test show that there is a significant influence between Environment-Based Interactive Multimedia and student learning outcomes. It was concluded that Environment-Based Interactive Multimedia is feasible and can improve student learning outcomes.